2007
DOI: 10.1002/art.22399
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of meningococcal c vaccination in juvenile idiopathic arthritis

Abstract: Objective. To determine whether vaccinations aggravate the course of autoimmune diseases such as juvenile idiopathic arthritis (JIA) and whether the immune response to vaccinations may be hampered by immunosuppressive therapy for the underlying disease.Methods. In this multicenter cohort study, 234 patients with JIA (ages 1-19 years) were vaccinated with meningococcal serogroup C (MenC) conjugate to protect against serogroup C disease (caused by Neisseria meningitidis). Patients were followed up for disease ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 49 publications
1
38
0
2
Order By: Relevance
“…The safety and short-term immunogenicity of the NeisVac-C vaccine has been studied previously in 234 JIA patients 10. The vaccine was found to be safe with no effect on disease activity, and showed good short-term immunogenicity with all patients having protective functional antibodies (SBA titre ≥8).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The safety and short-term immunogenicity of the NeisVac-C vaccine has been studied previously in 234 JIA patients 10. The vaccine was found to be safe with no effect on disease activity, and showed good short-term immunogenicity with all patients having protective functional antibodies (SBA titre ≥8).…”
Section: Discussionmentioning
confidence: 98%
“…The MenCC vaccine has proven to induce MenC-specific antibodies with bactericidal capacity in all JIA patients at 3 months after vaccination 10. However, the long-term persistence of MenC-specific antibodies is still uncertain 9.…”
mentioning
confidence: 99%
“…Both of them showed that the measles, mumps, and rubella booster vaccination was safe in JIA patients, including those who were taking prednisone, MTX, or etanercept (17,18). Studies of effects of inactivated vaccines, including influenza vaccine (19,20), hepatitis B vaccine (21), and meningococcal C vaccine (22), have not shown changes in disease activity or an increase in the occurrence of flares after vaccination in patients with JIA.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccinated healthy children were shown to experience more limb symptoms after the measles, mumps and rubella (MMR) vaccination, and a small number developed acute arthritis 3. The meningococcal C, influenza and hepatitis B vaccines seem to be safe to use in patients with juvenile idiopathic arthritis (JIA) and rheumatoid arthritis (RA) 4 – 6…”
mentioning
confidence: 99%